Effects of Quercetin in a Rat Model of Hemorrhagic Traumatic Shock and Reperfusion - Virginia Chamorro; Rachele Pandolfi; Laura Moreno; Bianca Barreira; Andrea Martínez-Ramas; Daniel Morales-Cano; Jesús Ruiz-Cabello; José Angel Lorente; Juan Duarte; Ángel Cogolludo; José Luis Alvarez-Sala; Francisco Perez-Vizcaino (Molecules, 2016)
Background: We hypothesized that treatment with quercetin could result in improved hemodynamics, lung inflammatory parameters and mortality in a rat model of hemorrhagic shock. Methods: Rats were anesthetized (80 mg/kg ketamine plus 8 mg/kg xylazine i.p.). The protocol included laparotomy for 15 min (trauma), hemorrhagic shock (blood withdrawal to reduce the mean arterial pressure to 35 mmHg) for 75 min and resuscitation by re-infusion of all the shed blood plus lactate Ringer for 90 min. Intravenous quercetin (50 mg/kg) or vehicle were administered during resuscitation. Results: There was a trend for increased survival 84.6% (11/13) in the treated group vs. the shock group 68.4% (13/19, p > 0.05 Kaplan–Meier). Quercetin fully prevented the development of lung edema. The activity of aSMase was increased in the shock group compared to the sham group and the quercetin prevented this effect. However, other inflammatory markers such as myeloperoxidase activity, interleukin-6 in plasma or bronchoalveolar fluid were similar in the sham and shock groups. We found no bacterial DNA in plasma in these animals. Conclusions: Quercetin partially prevented the changes in blood pressure and lung injury in shock associated to hemorrhage and reperfusion.